2019
DOI: 10.1177/0018578719836643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist-Led Procalcitonin-Guided Antibiotic Therapy in Critically Ill Patients With Pneumonia

Abstract: Purpose: Procalcitonin (PCT) is a peptide that is released in response to bacterial infections. The 2016 Infectious Diseases Society of America pneumonia guidelines recommend PCT monitoring to help guide antibiotic discontinuation. Utilization of PCT is well described in the literature; however, there is a paucity of literature regarding pharmacists’ involvement for using PCT in antibiotic interventions. The objective of this study was to investigate the effect of pharmacist-led intervention with PCT-guided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Because we previously experienced success with a PCT algorithm in our institution in reducing antibiotic therapy for critically ill patients with pneumonia, simplification of the algorithm and expanding its use to sepsis helped with awareness and adherence among our critical care providers. 13 This study has several limitations. This was a singlecenter study with a small sample size.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Because we previously experienced success with a PCT algorithm in our institution in reducing antibiotic therapy for critically ill patients with pneumonia, simplification of the algorithm and expanding its use to sepsis helped with awareness and adherence among our critical care providers. 13 This study has several limitations. This was a singlecenter study with a small sample size.…”
Section: Discussionmentioning
confidence: 92%
“…12 Recently, our institution incorporated a PCT algorithm with pharmacists' interventions in patients with community-acquired pneumonia, and observed reduction in antibiotic duration of therapy. 13 This current study evaluated the impact of pharmacist recommendations utilizing a more simplified PCT algorithm on critically ill patients and expanded indications to sepsis or septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…While data exist highlighting the utility of pharmacist-driven procalcitonin protocols, the impact of a clinical-decision support tool such as the pharmacist Daily Checklist embedded in an electronic health record has not been as well documented [18][19][20]. This project aims to validate the effectiveness of this clinical decision support tool following the conversion from ASP-driven interventions to clinical pharmacist-led stewardship.…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that 30-80% of antibiotic provision were not based on accurate indication, which can further increase bacterial resistance, treatment costs, morbidity, and mortality [11], [12]. Many other pharmacy intervention studies on the usage of wide range of antibiotics and varied purposes in the treatment of pneumonia patients have been undertaken elsewhere [10], [13], [14], [15]. Furthermore, efforts to avoid inappropriate use of antibiotics in all areas of the world are important to maximize clinical outcomes, minimize side effects, avoid toxicity, reduce treatment costs, and most importantly to reduce the global emergence of bacterial resistance [16].…”
Section: Introductionmentioning
confidence: 99%